2023
DOI: 10.3390/foods12142770
|View full text |Cite
|
Sign up to set email alerts
|

Is Corporate Social Responsibility Considered a Marketing Tool? Case Study from Customers’ Point of View in the Slovak Food Market

Abstract: The paper aims at the question of using Corporate Social Responsibility (CSR) activities as a marketing tool from the customers’ perspective in the Slovak food market. Five research questions and hypotheses were set to reach the given aim. The research was based on a questionnaire survey with 1254 respondents. The frequency and contingency tables were used to evaluate the obtained data, one sample proportion Z test, Pearson Chi-square test, and Spearman’s rank correlation coefficient. Based on the results, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Regular milk and milk-based products have been criticized, as the production and processing of these products are associated with deforestation and high carbon and water footprints, resulting from greenhouse gas emissions and water pollution [27,28]. Environmentally responsible consumers are aiming to reduce their impact on the environment through their product choices and buying behavior [29,30]. As these consumers are knowledgeable about environmental issues and have positive attitudes towards environmentally friendly product alternatives, they demand transparency and verification concerning production processes [29].…”
Section: Environmental Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular milk and milk-based products have been criticized, as the production and processing of these products are associated with deforestation and high carbon and water footprints, resulting from greenhouse gas emissions and water pollution [27,28]. Environmentally responsible consumers are aiming to reduce their impact on the environment through their product choices and buying behavior [29,30]. As these consumers are knowledgeable about environmental issues and have positive attitudes towards environmentally friendly product alternatives, they demand transparency and verification concerning production processes [29].…”
Section: Environmental Concernsmentioning
confidence: 99%
“…Animal welfare has been widely discussed in the US dairy industry, media, and a plethora of academic studies. Agricultural consumer studies have indicated that the practices of dairy farms are raising consumer concerns and criticisms [23,[29][30][31]. These include inappropriate flooring and pasture access, separating calves from their mothers too early, the quality of neonatal care, and dehorning or tail docking without anesthesia [31][32][33].…”
Section: Animal Welfare Concernsmentioning
confidence: 99%
“…Accordingly, the e-commerce platform shall seek to improve the efficiency of undertaking CSR. (5) The demand for e-commerce platform in all three sales modes increases as the potential market size of the e-commerce platform increases, the consumers' sensitivity to the CSR input level increases, or the CSR input cost coefficient decreases, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…The specific model structure is shown in Figure 1, and the symbols used in this paper and their relevant meanings are shown in Table 1. In addition, this paper makes the following assumptions: (1) We assume that the manufacturer's production cost, transportation cost, and transportation cost of the e-commerce platform are 0; (2) We assume that the information among the manufacturer, the offline retailer, and the e-commerce platform is entirely symmetric; (3) We assume that the market size is standardized to 1; (4) We assume that the influence of CSR undertaken by the e-commerce platform on its demand is greater than that of the offline retailer, that is, λ > β; (5) The cost of the e-commerce platform undertaking CSR is 1 2 εe 2 ; the greater ε is, the higher the CSR input cost [23]. Selling price for a product of offline retailer p e…”
Section: Problem Description and Model Hypothesismentioning
confidence: 99%
See 1 more Smart Citation